THE UNIFORMLY SUMMATION OF BIORTHOGONAL EXPANSIONS BY THE INCOMPLETE SYSTEM OF RATIONAL FUNCTIONS IN HARDY’S SPACES - Martirosyan, M. S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2004)
The biorthogonal expansions in Hardy’s H^p( 1<p<∞) spaces by the incomplete system of rational functions are uniformly summated on the compact subsets of complex plane on positive distance from the set of poles of system’s functions.